Frequent falls and confusion: recurrent hypoglycemia in a patient with tuberous sclerosis complex. Issue 5 (24th March 2018) - Comninos, Alexander N.; Yang, Lisa; Abbara, Ali; Dhillo, Waljit S.; Bassett, J.H. Duncan; Todd, Jeannie F.
Key Clinical Message: Recurrent hypoglycemia is common, but its presentation is often insidious resulting in delays in diagnosis and significant morbidity. We describe a case of an insulinoma presenting with falls and confusion in a patient with tuberous sclerosis, demonstrating the importance of early hypoglycemia identification and a potential shared molecular pathogenesis. Abstract : Recurrent hypoglycemia is common, but its presentation is often insidious resulting in delays in diagnosis and significant morbidity. We describe a case of an insulinoma presenting with falls and confusion in a patient with tuberous sclerosis, demonstrating the importance of early hypoglycemia identification and a potential shared molecular pathogenesis.